Effects of polyphenolic fraction of silymarin on lipoprotein profile in rats fed cholesterol-rich diets - Skottová, Nina; Vecera, Rostislav; Urbánek, Karel; Vána, Petr; Walterová, Daniela; Cvak, Ladislav (Pharmacological research, 2003)
To study the influence of polymerised polyphenolics (PP), a fraction of silymarin (SM), on lipids and oxidant status, rats were fed high-cholesterol (1%), high-fat (10%) diets containing either lard fat (LFD) rich in saturated/monounsaturated fatty acids, or currant oil (COD) rich in polyunsaturated fatty acids. PP and SM were administered as dietary supplements (0.1-0.5-1.0%) for 3 weeks. PP (1%) decreased cholesterol (C) in VLDL (from 0.72+/-0.08 mmol l(-1) in LFD control to 0.35+/-0.07 mmol l(-1), P<0.01, and from 0.33+/-0.05 mmol l(-1) in COD control to 0.09+/-0.02 mmol l(-1), P<0.001), and increased HDL-C/VLDL-C ratio, however, without effect on the total plasma C and LDL-C. Liver C content (LFD 19.32+/-1.50 micromol g(-1), COD 18.64+/-2.13 micromol g(-1), N.S.) decreased after PP (1%) to 12.24+/-0.76 micromol g(-1), P<0.01, and 8.78+/-0.95 micromol g(-1), P<0.001, respectively. Triacylglycerols (TAG) in plasma and VLDL decreased after PP in the LFD group only, which displayed higher TAG levels than the COD group. Likewise, LFD caused a higher liver TAG content than did COD (31.16+/-3.00 micromol g(-1) versus 17.31+/-1.48 micromol g(-1), P<0.01), and PP (1%) decreased liver TAG only in rats fed LFD (19.55+/-2.43 micromol g(-1), P<0.02). Blood glutathione (GSH) increased after PP (1%) in the LFD group from 0.97+/-0.11 to 1.54+/-0.19 mmol l(-1) (P<0.05) and in the COD group from 0.58+/-0.15 to 1.23+/-0.10 mmol l(-1) (P<0.01), while liver GSH and plasma TBARS did not change. On principle, effects of PP were dose-dependent and parallel to SM. These results suggest that the polyphenolic fraction of SM positively modifies lipoprotein profile, counteracts the development of fatty liver and ameliorates an antioxidant status in circulation.
Keywords: Silymarin; Lipoproteins; Male; Rats, Wistar; lipoproteiny; cholesterol dietní; Cholesterol, Dietary; mužské pohlaví; Dietary Fats; potkani Wistar; fenoly; silymarin; Polymers; krysa rodu Rattus; dietní tuky; Animals; játra; flavonoidy; polymery; zvířata; Rats; Flavonoids; Liver; Phenols